Pemberdayaan Masyarakat Melalui Pengembangan Objek Wisata Umbul Pelem Waterpark - Ratih, Ayu Mustika; Trinugraha, Yosafat Hermawan (FISIP Universitas Malikussaleh, 2025)
This research aims to determine the process of community empowerment through the development of the Umbul Pelem Waterpark tourist attraction in Wunut Village and determine the supporting and inhibiting factors. This research uses descriptive qualitative research with a case study method. The informants in this research consisted of the Head of Wunut Village, Director of BUMDes Sumber Kamulyan, Employees of BUMDes Sumber Kamulyan, and Wunut Village Community. Data collection techniques are observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The research results show that the process of empowering the Wunut Village community is carried out through three stages, namely the awareness stage, capacity building stage, and empowerment. There are supporting and inhibiting factors for community empowerment through the development of Umbul Pelem. The supporting factors are the existence of the Umbul Pelem natural spring which is still maintained today and the enthusiasm of the community regarding the development of the Umbul Pelem tourist attraction as an effort to empower the community. The inhibiting factor is that there are differences in community opinion regarding the progress of the community empowerment program being carried out and there is still a lack of skills training for empowered communities in Umbul Pelem. The community empowerment program carried out through the development of the Umbul Pelem Waterpark tourist attraction is able to improve the community's economy and community welfare.